2021
DOI: 10.2147/ndt.s341782
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbances and Associated Factors in Drug-Naïve Patients with Parkinson’s Disease

Abstract: Purpose Sleep disturbance is one of the common symptoms in Parkinson’s disease (PD). The study of sleep disturbance used to concentrate on treated PD. This study aimed to investigate the factors that are associated with the sleep quality of drug-naïve patients with PD. Patients and Methods All participants were interviewed using a standard questionnaire to collect basic information. PD severity, depression symptoms, anxiety symptoms, sleep quality, cognitive status, lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Low sleep status score, daily use of levodopa, high Hoehn and Yahr stage, high UPDRS II score, and high UPDRS III score were risk factors for depression in these PD patients. Clinical research 24 has found that 67%-98% of PD patients have a sleep disorder, and sleep disorders are the main cause of daytime sleepiness and cognitive impairment, which have significant adverse effects on a patient’s daily life and psychological state. Therefore, sleep disorders are speculated to be associated with depression in PD patients, and a later study confirmed that sleep status scores are negatively correlated with depression.…”
Section: Discussionmentioning
confidence: 99%
“…Low sleep status score, daily use of levodopa, high Hoehn and Yahr stage, high UPDRS II score, and high UPDRS III score were risk factors for depression in these PD patients. Clinical research 24 has found that 67%-98% of PD patients have a sleep disorder, and sleep disorders are the main cause of daytime sleepiness and cognitive impairment, which have significant adverse effects on a patient’s daily life and psychological state. Therefore, sleep disorders are speculated to be associated with depression in PD patients, and a later study confirmed that sleep status scores are negatively correlated with depression.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in melatonin rhythmicity are also implicated in RBD in PD (Weissov a et al, 2018): Although some studies have failed to observe a significant difference in the 24-h melatonin rhythm between RBD patients and healthy controls (Breen et al, 2014), other results indicate that melatonin rhythmicity differs between PD/RBD patients and controls in that the melatonin rhythm is delayed by approximately 2 h, in parallel with a 1 h delay in habitual sleep phase (Weissov a et al, 2018). These findings suggest that previously reported inconsistent findings regarding alteration in the circadian phase in PD as derived from DLMO or core body measurements (Bolitho et al, 2014;Videnovic et al, 2014;Zhong et al, 2021) may be partly due to differing clinical characteristics of the cohorts examined in terms of medication status, disease severity and presence of RBD.…”
Section: Circadian Rhythms In Parkinson' S Diseasementioning
confidence: 94%